2016
DOI: 10.1016/j.marpolbul.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Local bleaching thresholds established by remote sensing techniques vary among reefs with deviating bleaching patterns during the 2012 event in the Arabian/Persian Gulf

Abstract: A severe bleaching event affected coral communities off the coast of Abu Dhabi, UAE in August/September, 2012. In Saadiyat and Ras Ghanada reefs ~40% of the corals showed signs of bleaching. In contrast, only 15% of the corals were affected on Delma reef. Bleaching threshold temperatures for these sites were established using remotely sensed sea surface temperature (SST) data recorded by MODIS-Aqua. The calculated threshold temperatures varied between locations (34.48 °C, 34.55 °C, 35.05 °C), resulting in site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…More recently, focus has shifted toward understanding the plasticity of thermal tolerance in corals, and numerous studies have identified a direct link between thermal preconditioning and bleaching susceptibility from both field observations (Castillo and Helmuth, 2005;Maynard et al, 2008;Thompson and van Woesik, 2009;Castillo et al, 2012;Shuail et al, 2016) and experimental manipulation (Brown et al, 2000(Brown et al, , 2002Dove et al, 2006;Middlebrook et al, 2008;Bellantuono et al, 2012b;Bay and Palumbi, 2015). For example, Acropora, Pocillopora, and Porites from the Great Barrier Reef showed lower rates of bleaching during the 2002 bleaching event than the 1998 event, despite more intense conditions during the 2002 event (Maynard et al, 2008).…”
Section: Thermal History and Bleaching Susceptibilitymentioning
confidence: 99%
“…More recently, focus has shifted toward understanding the plasticity of thermal tolerance in corals, and numerous studies have identified a direct link between thermal preconditioning and bleaching susceptibility from both field observations (Castillo and Helmuth, 2005;Maynard et al, 2008;Thompson and van Woesik, 2009;Castillo et al, 2012;Shuail et al, 2016) and experimental manipulation (Brown et al, 2000(Brown et al, , 2002Dove et al, 2006;Middlebrook et al, 2008;Bellantuono et al, 2012b;Bay and Palumbi, 2015). For example, Acropora, Pocillopora, and Porites from the Great Barrier Reef showed lower rates of bleaching during the 2002 bleaching event than the 1998 event, despite more intense conditions during the 2002 event (Maynard et al, 2008).…”
Section: Thermal History and Bleaching Susceptibilitymentioning
confidence: 99%
“…The Persian/Arabian Gulf (PAG) is a thermally extreme and hypersaline body of water with temperatures regularly exceeding 34 • C during summer in its southern and hottest part (Hume et al, 2013;Shuail et al, 2016; Figure 1, Figure S1), temperatures that prove fatal to most tropical corals (Coles and Riegl, 2013;Hume et al, 2013). Yet, thriving coral communities are found along its coastline (Coles, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Such increases are causing more frequent and severe coral bleaching events (Logan et al, 2014) during which the obligate symbiotic relationship between coral and algal symbiont (genus Symbiodinium) breaks down leading to symbiont loss, and if recovery is not timely, death of the host (Hughes et al, 2003). Temperature thresholds at which these bleaching events occur are dependent on host and symbiont genotypes but typically lie 1 • C above the average maximum summer temperature for a reef (Goreau and Hayes, 1994;Shuail et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data, along with data from published literature (Purser, 1973;Sheppard, 1988;Fatemi and Shokri, 2001;Rezai et al, 2004Rezai et al, , 2010Purkis and Riegl, 2005;Aramco, 2007;Burt et al, 2011Burt et al, , 2013Kavousi et al, 2011;Foster et al, 2012;Riegl and Purkis, 2012;Bauman et al, 2013Bauman et al, , 2014Mohammadizadeh et al, 2013;Grizzle et al, 2016;Shuail et al, 2016), were used to produce Figure 1.…”
Section: Environmental Conditions and Coral Conditionmentioning
confidence: 99%